Chronic Left Epididymo-Orchitis Complicated by Pyocele: A Rare Presentation - Supriya, Guntennagari; Battula, Pradeep; Masood, Shaik Ontela; Jyothirmai, Sane; Durga, Pennakanti; Reddy, Vemareddy Ahindra (Indian Journal of Pharmacy Practice)
Epididymitis and epididymo-orchitis are common diseases that present with swelling in the scrotum and are mostly seen in surgical outpatient departments. Epididymitis and epididymo-orchitis normally resolve after adequate antibiotic treatment, although it may lead to several complications. Scrotal pyoceles are uncommon purulent collections in the potential space between the visceral and parietal tunica vaginalis surrounding the testicle. We present a case of epididymo-orchitis that progressed to pyocele despite antibiotic treatment. Through clinical, physical, and radiographical evaluation and by intraoperative findings, he was diagnosed with chronic left epididymo-orchitis with pyocele. A left orchidectomy was performed that helps to prevent further complications.
Keywords: Epididymo-Orchitis; Pyocele; Testicular abscess; Orchidectomy